Tao of Communication: Developing a Gender-Balanced Husband-Wife Communication Model at KUA North Tambun - Aryadillah Aryadillah; Mirza Ronda; Ridzki Rinanto Sigit; Marlinda Irwanti Poernomo (DAWUH : Islamic Communication Journal, 2026)
Communication between men and women is a social phenomenon closely linked to gender construction, culture, and existing value systems in society. Differences in mindset, language use, and conversation patterns between the two sexes often lead to communication imbalances that lead to interpersonal conflict, discrimination, domination, and even exploitative relationships. The paradigm of male communication dominance, which remains the social standard across various cultural levels, reinforces the emergence of subordinate relationships between husbands and wives. This situation contributes to increased domestic conflict, including divorce caused by poor communication, inability to resolve conflicts, domestic violence, infidelity, and incompatible values. This study used the R&D (Research and Development) method using Derek Rowntree's development model. Based on expert assessments, 86% of this product or model is suitable and effective for use. The Tao of Communication Model is expected to improve interpersonal relationships (especially between husbands and wives), reduce communication conflicts that lead to disputes and divorce, and reduce, or even reduce, the ever-increasing divorce rate.